KESIAPAN SEKOLAH DALAM MENGIMPLEMENTASIKAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) - Yusuf, Amin (Lembaran Ilmu Kependidikan, 2007)
A number of schools in Semarang have been trying to implement theKTSP. However, schools still struggle to understand the curriculum. Thegovernment has stated that schools which are ready can implement the KTSP by2007, and those which are not can postpone the implementation until the end of2009/2010. A study of the schoolsÃ¢â¬â¢ readiness to implement the KTSP wasconducted at four schools in Semarang. The research aims at (1) describing theschoolsÃ¢â¬â¢ readiness to implement the KTSP; (2) identifying the needs of theschool to implement the KTSP; (3) finding out the supporting and inhibitingfactors of the KTSP implementation. The readiness to implement the KTSPvaried from one school to another. The varieties include several aspects, suchas: curriculum properties, facilities, finance, environment, principalÃ¢â¬â¢sleadership, teachers and staffsÃ¢â¬â¢ readiness, and parents and studentsÃ¢â¬â¢ readiness. Itwas also revealed that what were needed by the schools to implement the KTSPwere commitment and financial support from the government and teachersÃ¢â¬â¢understanding of the curriculum through training. The inhibiting factor wasinconsistent policy.Kata Kunci: Kesiapan, Implementasi, dan KTSP